TREW Gear : is Amazon the trail to growth? - Lecinski, Jim; Bouchez, Helena (London : Kellogg School of Management, 2022)
Chris Pew, an expert backcountry skier, was a founder and the CEO of 12-year-old TREW Gear, a premium niche brand for technical backcountry ski apparel. TREW Gear's products--snow bibs, jackets, pants, and accessories--were selling well through independent and specialty retailers and direct to consumers on trewgear.com. Heavy on Pew's mind, however, was how to continue growing the business, particularly the question of whether he should start selling TREW on Amazon.com. Would TREW's presence on the behemoth US-based e-commerce platform help the company grow, long-term? Shorter-term, would selling on Amazon deliver the 20% increase in revenues his investors wanted to see by the end of the year? And if Amazon wasn't the best choice, what distribution strategy should he embrace?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporations -- Growth